Identification, Characterization, and Expression Profile Analysis of the mTERF Gene Family and Its Role in the Response to Abiotic Stress in Barley (Hordeum vulgare L.) - Li, Tingting; Pan, Wenqiu; Yuan, Yiyuan; Liu, Ying; Li, Yihan; Wu, Xiaoyu; Wang, Fei; Cui, Licao (Frontiers in Plant Science, 2021)
Plant mitochondrial transcription termination factor (mTERF) regulates organelle gene expression and is functionally characterized in diverse species. However, limited data are available about its functions in the agriculturally important cereal barley (Hordeum vulgare L.). In this study, we identified 60 potential mTERFs in the barley genome (HvmTERFs) through a comprehensive search against the most updated barley reference genome, Morex V2. Then, phylogenetic analysis categorized these genes into nine subfamilies, with approximately half of the HvmTERFs belonging to subfamily IX. The conserved motifs and exon-intron structure organization were systematically analyzed and strongly supported the current predictions. Both segmental and tandem duplication contributed to the expansion of HvmTERFs, and the duplicated gene pairs were subjected to strong purifying selection. Expression analyses showed that HvmTERFs were widely involved in various aspects of barley development and tolerance to diverse stresses. The induction of 25 candidate HvmTERFs was confirmed under abiotic stress and phytohormone treatment via qRT-PCR. Finally, a small nucleotide diversity loss was observed for HvmTERFs during the domestication of barley. Collectively, this is the first report to characterize HvmTERFs, which will not only provide important insights into further evolutionary studies but also contribute to a better understanding of the potential functions of HvmTERFs and ultimately will be useful in future gene functional studies.